Aerodynamic and Structural Analysis of Ceiling Fan for Different Blade Materials. (2018) - Dhurvey, Priyanka; Kumar Pathak, Neeraj; Soni, Sanjay; Pandey, Ajay
Abstract: Creating a breeze in a space is necessary to enhance convective heat transfer and accordingly body heat dissipation. In most tropical countries fan are extensively used to create indoor breeze, improve the space air distribution and hence enhance the feeling of comfort. The fan speed, diameter, number of blades, blade angle and location, all play an important role in determining the induced flow pattern features in the space. In present work analytical calculations are performed to calculate the coefficient of performance, estimate the net air flow per unit power input for four different blade materials namely steel, aluminium, GFRP composite and PVC. The ceiling fan model is created in CREO elements/Pro 5.0 and the whole geometry is imported into ANSYS CFX. Profile GM 15 airfoil is selected for the blade analysis. The ceiling fan simulation is done for the entire fan model including blade behaviour due to aerodynamic lift and drag forces which also accompanied by bending stresses and deflection. The comparisons for the combined loads are studied for better stability and performance of the blade for different materials. ANSYS APDL software is used to do the structural and modal analysis. At last, the monthly and yearly power consumption by ceiling fan for different blade materials is also calculated.